2010
DOI: 10.1111/j.1442-2050.2010.01087.x
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal verrucous carcinoma arising from hyperkeratotic plaques associated with human papilloma virus type 51

Abstract: Esophageal verrucous carcinoma is a rare variant of esophageal squamous cell carcinoma. We report a case of esophageal verrucous carcinoma associated with human papilloma virus (HPV) type 51. The patient had long-standing dysphagia and odynophagia, and white esophageal plaques showing hyperkeratosis on biopsy. At repeat endoscopy, the esophagus was covered with verrucous white plaques and areas of nodular mucosa with white fronds, with a distal 10-cm smooth mass protruding into the lumen. Biopsies demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
35
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 12 publications
2
35
1
1
Order By: Relevance
“…9 Intraepithelial neutrophilic infiltration and intraepithelial neutrophilic microabscess are consistent findings in our current study, in both the resected and endoscopic mucosal biopsies with carcinoma cuniculatum. The presence of neutrophilic inflammation and Candida organisms in endoscopic mucosal biopsies taken from an obvious esophageal mass should prompt a search for evidence of a well-differentiated squamous cell carcinoma such as carcinoma cuniculatum or verrucous carcinoma, as supported by our current series and the report by Tonna et al 8 The neutrophilic inflammation in the esophageal carcinoma cuniculatum may be due to superimposed Candida infection, bacterial overgrowth, local irritation/trauma secondary to obstruction, or an inflammatory response associated with the neoplastic process per se as it is also present in cases of carcinoma cuniculatum without Candida infection or bacterial overgrowth. While the exact mechanism of this intraepithelial neutrophilic infiltration remains unclear, a few previous studies appear to support that overexpression of transforming growth factor-b1 (TGFb1) in squamous cell neoplasm/ carcinoma may lead to neutrophilic inflammation via an interleukin 17 (IL-17)-dependent signaling pathway.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…9 Intraepithelial neutrophilic infiltration and intraepithelial neutrophilic microabscess are consistent findings in our current study, in both the resected and endoscopic mucosal biopsies with carcinoma cuniculatum. The presence of neutrophilic inflammation and Candida organisms in endoscopic mucosal biopsies taken from an obvious esophageal mass should prompt a search for evidence of a well-differentiated squamous cell carcinoma such as carcinoma cuniculatum or verrucous carcinoma, as supported by our current series and the report by Tonna et al 8 The neutrophilic inflammation in the esophageal carcinoma cuniculatum may be due to superimposed Candida infection, bacterial overgrowth, local irritation/trauma secondary to obstruction, or an inflammatory response associated with the neoplastic process per se as it is also present in cases of carcinoma cuniculatum without Candida infection or bacterial overgrowth. While the exact mechanism of this intraepithelial neutrophilic infiltration remains unclear, a few previous studies appear to support that overexpression of transforming growth factor-b1 (TGFb1) in squamous cell neoplasm/ carcinoma may lead to neutrophilic inflammation via an interleukin 17 (IL-17)-dependent signaling pathway.…”
Section: Discussionsupporting
confidence: 79%
“…Our results are in line with a previous study, which showed that nonpapillary squamous high-grade dysplasia was only present in the deep portion of the tumor but not the superficial endoscopic mucosal biopsy from verrucous carcinoma of the esophagus, a closely related variant of well-differentiated squamous cell carcinoma. 8 Conventional diagnostic criteria of Esophageal carcinoma cuniculatum esophageal squamous cell carcinoma used by pathologists for endoscopic mucosal biopsy are heavily based on the presence of deep keratinization and atypia, particularly marked nuclear atypia, which may explain the low sensitivity of 9% observed in our study prior to our semiquantitative histologic assessment. In this study, the original endoscopic biopsies were diagnosed as esophagitis or non-specific inflammation on 17 occasions including eight diagnoses of fungal esophagitis or changes suggestive of fungal esophagitis.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Nos últimos anos, entretanto, artigos da literatura especializada vêm mostrando a presença do DNA do HPV em amostras de tecido de carcinomas do esôfa-go 13 , estômago 14,15 , pulmão 14 , mama 16 e colorretal [17][18][19] . O HPV foi detectado em até 37,5% dos adenocarcinomas gástricos 15 , e em 27,8% dos CEC esofágicos 20 , havendo diferença em áreas de alta e de baixa prevalência para esse tumor maligno (65 e 6%, respectivamente) 21 .…”
unclassified